PENINGKATAN PROFESIONALISME GURU DALAM MENGGUNAKAN TEKNOLOGI PADA PENYUSUNAN BANK SOAL BERBASIS LITERASI DAN NUMERASI DI YPN BELINYU - Baiq Desy Aniska Prayanti; Lasmi Hartati; Nurhaeka Tou; Putri Mentari Endraswari (Jurnal Abdi Insani, 2023)
The role of information technology in the preparation of the question bank at this time is really needed and required. Considering that in the current era technology has become the main subject in various activities. Technology can facilitate the implementation of literacy and numeracy-based learning and evaluation processes. The ability of teachers in mastering technology, especially in preparing literacy and numeracy-based question banks, is currently an obstacle experienced by the Belinyu National Education Foundation (YPN). Teachers are required to have understanding and ability to integrate technology in the learning process. This activity aims to provide training to teachers in compiling literacy and numeracy-based question banks by utilizing Wordwall and Kahoot technology. This technology is a game-based learning media. The method used in this service is lecture and practice. Presentation of literacy and numeracy-based material is presented first so that teachers get an understanding of the material. After that, the Wordwall and Kahoot technology materials were immediately practiced on each teacher's computer. Based on the results of the activities through simulations and practice, there is a difference between before the material is delivered and after the material is delivered. This can be seen from the results of the pre-test (45%) where respondents answered that they did not often use technology in compiling the question bank and the results of the post-test (65%) showed that respondents agreed and were interested in the training. The teachers are starting to be interested in game-based Wordwall and Kahoot technologies as described. In addition, teachers can also directly create literacy and numeracy-based questions which are then presented in Wordwall and Kahoot media. Based on the results of the pre-test and post-test, Wordwall and Kahoot are learning innovations that can be applied in the teaching and learning process.